Association Between Shift Work and Acute Coronary Syndrome According to Alcohol Intake and Smoking - Seok-Jin Ryu; Sun-Min Kim; Hyun-Yi Kook; Eun-Young Park; Eujene Jung (Medicina)
Background and Objectives: Shift work is associated with an increased risk of acute coronary syndrome (ACS) and higher rates of smoking and alcohol consumption. This study examines how smoking and alcohol intake may influence the effect of shift work on ACS risk, indicating a complex interaction among these factors in individuals engaged in shift work. Materials and Methods: This investigation utilized data from the Korean Genome and Epidemiology Study (KoGES). Shift work was the primary exposure, and the main outcome was ACS, defined as either myocardial infarction or angina pectoris diagnosed from 2003 to 2020. Cox proportional regression analysis was employed to assess the impact of shift work, smoking, and alcohol intake on ACS incidence. Additionally, we performed an interaction analysis to examine the effects of shift work in conjunction with smoking and alcohol intake on ACS incidence. Results: Out of 10,038 participants enrolled during the study period, 3696 (36.8%) met the inclusion criteria. The incidence rate of ACS was 11.88 per 1000 person-years in the shift work group compared to 5.96 per 1000 person-years in the non-shift work group. Using Cox proportional logistic regression, shift work was found to be associated with a hazard ratio (HR) of 1.74 (95% CI, 1.20, 2.53) compared to the non-shift work group. Smoking and alcohol consumption did not exhibit a significant HR for ACS incidence, with HRs of 1.31 (95% CI, 0.98, 1.75) and 0.83 (95% CI, 0.65, 1.07), respectively. In the interaction model, after adjusting for other covariates, shift work was not significantly associated with ACS incidence in current smokers (HR 1.05, 95% CI 0.49, 2.23). However, among non-current smokers, shift work emerged as a significant risk factor for ACS incidence (HR 2.26, 95% CI 1.44, 3.55) (p for interaction < 0.01). No interaction was found between alcohol consumption and shift work in relation to ACS incidence. Conclusions: Shift work is an independent risk factor for acute coronary syndrome (ACS), particularly among non-current smokers. This finding highlights the need to address both lifestyle and occupational factors when developing strategies to mitigate ACS risk among shift workers. Employers and policymakers should consider implementing targeted workplace interventions to reduce this risk. These may include optimizing shift schedules to minimize circadian disruption, providing regular health screenings focused on cardiovascular health, and promoting healthy lifestyle habits such as balanced nutrition, regular physical activity, and stress management programs. Additionally, workplace wellness initiatives could focus on reducing other modifiable risk factors, such as providing resources for smoking cessation and limiting exposure to occupational stressors. Integrating these strategies into occupational health policies can contribute to the early detection and prevention of ACS, ultimately improving the cardiovascular health of shift workers.